Effectiveness of home based intervention program in reducing mortality of hip fracture patients: A non-randomized controlled trial. (March 2019) - Mahran, Dalia G; Farouk, Osama; Ismail, Mervat A; Alaa, Mohamed M; Eisa, Amr; Ragab, Islam I
Highlights: The study was conducted to examine the effectiveness of a postoperative intervention program in reducing the mortality and improving mobility in hip fracture patients over one year. A non randomized controlled trial study with follow up of one hundred twenty four admitted hip fracture patients aged 50 years and older to a trauma Unit. The intervention was a postoperative care program in the form of education sessions with an explanatory leaflet on discharge for nutrition and physical exercise program at home. Follow up phone calls were done at 3 months, 6 months and one year postoperative by one assessor. Physical mobility was assessed by 24 items Western Ontario And McMaster Universities Osteoarthritis Index (WOMAC). A significant improvement in mobility and reduction of mortality were achieved by the postoperative care program that could be incorporated into the hip fracture patients' care pathway. Abstract: Purpose: The study was done to investigate whether a postoperative intervention program is effective in reducing mortality and improving mobility in two comparative hip fracture patients over one year postoperatively. Methods: A non-randomized controlled trial study with an intervention group of hip fracture patients and historical control group with 12 months follow up. One hundred twenty four admitted hip fracture patients to the Trauma Unit of Assiut University Hospitals, aged 50 years and older were included from 1st July to 31st December 2014. They were divided into 64 and 60 patients as intervention and control groups respectively. Weight, height and bone mineral density were measured and baseline characteristics were taken. The intervention was a postoperative care program in the form of education sessions with an explanatory leaflet on discharge for nutrition and physical exercise program at home. Follow up phone calls were done at 3 months, 6 months and one year postoperatively by one assessor. Physical mobility was assessed by 24 items Western Ontario And McMaster Universities Osteoarthritis Index (WOMAC). Results: Mortality was significantly higher in the control group, WOMAC score was significantly better among intervention group through follow up. By multivariate Cox survival analysis, advancing age, no intervention, osteoporosis, postoperative complications, chest infections and heart attacks were significant predictors for mortality. Conclusion: A significant improvement in mobility and reduction of mortality was achieved by application of a postoperative care program that could be incorporated into the hip fracture patients' care pathway.